2009
DOI: 10.1088/0953-2048/22/10/105010
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of non-self-spreading hotspots in current- and voltage-biased superconducting NbN microstrips

Abstract: Electrical transport measurements were performed on superconducting NbN multicontact microstrips in order to investigate non-equilibrium dissipative states in type-II nanostructures. Current-biased and voltage-biased approaches point out the ability to stabilize a normal phase that grows discontinuously, in opposition to the usual self-spreading hotspot propagation. Results obtained by applying a dc voltage to two segments in series support this idea of a peculiar hotspot expansion. This last voltage-biasing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The principle of operation of superconducting single photon detectors (SSPDs) are commonly based on the spread of a current assisted hotspot expected at low temperatures when phase slips become unstable. , In highlight of the previous analyses, this regime does not occur at the temperatures reached here (200 mK) that remain below the typical range of temperature for single photon detection (1–4 K).…”
mentioning
confidence: 85%
“…The principle of operation of superconducting single photon detectors (SSPDs) are commonly based on the spread of a current assisted hotspot expected at low temperatures when phase slips become unstable. , In highlight of the previous analyses, this regime does not occur at the temperatures reached here (200 mK) that remain below the typical range of temperature for single photon detection (1–4 K).…”
mentioning
confidence: 85%
“…In particular, the hysteresis is almost negligible if T > 0.4 • T C . In NbN nanowires the hysteresis, which also decreases when increasing the temperature [77], can instead persist up to temperatures close to T C . In our case, the narrower T /T C range in which I C > I r might be due to the smaller value of κ of YBCO with respect to that of NbN.…”
Section: Ultrathin Bare Nanowires: a Possible Platform For Ybco Singl...mentioning
confidence: 99%
“…The hysteresis current is defined as the smallest applied current sufficient to sustain a stable hot-spot region in a superconducting film. Its value, the shape of the current-voltage characteristics, and the temperature and geometry dependences have been the subject of many theoretical and experimental works [8][9][10][11]. It has been shown that in the case of long bridges the hysteresis current is mostly defined by a thermal resistance, or in other words by a transparency for phonon propagation through an interface between the superconducting film and the substrate.…”
Section: Introductionmentioning
confidence: 99%